ASSOCIATION NOTES. - Austin, E. Burl (The Accounting Review, 1957)
The article reports on the events in the field of accounting education. George Gibbs was reappointed to a four-year term on the state board of accountancy. E.I. Fjeld, formerly of the College of the City of New York, joined the staff in September as visiting professor of accounting. Willard Horwich was appointed assistant professor of accounting this fall. T. Leroy Mami conducted a three day Institute in Hospital Accounting under the auspices of the Mississippi Hospital Association at Gulf port in July. May Noel Barron returned to the campus after a 15-month leave of absence, during which time she served as assistant auditor for the State of Kentucky. Emerson C. Erb has been granted leave of absence for one year to continue work on his doctorate at Indiana University. William D. Tuxbury was added to the staff in September. H. Calvert Krueger has accepted a position at Arizona State College. Francis D. Jabara received his CPA certificate in Kansas last December. The Second Annual Petroleum Accounting Conference was held on the campus in May with over 250 persons attending.